Hannah Arendt and the Negro Question - Gines, Kathryn T., 1978- (Book collections on Project MUSE., 2014)
While acknowledging Hannah Arendt's keen philosophical and political insights, Kathryn T. Gines claims that there are some problematic assertions and oversights regarding Arendt's treatment of the ""Negro question."" Gines focuses on Arendt's reaction to the desegregation of Little Rock schools, to laws making mixed marriages illegal, and to the growing civil rights movement in the south. Reading them alongside Arendt's writings on revolution, the human condition, violence, and responses to the Eichmann war crimes trial, Gines provides a systematic analysis of anti-black racism in Arendt's